Translesion Synthesis in Plants: Ultraviolet Resistance and Beyond - Sakamoto, Ayako N. (Frontiers in Plant Science, 2019)
Plant genomes sustain various forms of DNA damage that stall replication forks. Translesion synthesis (TLS) is one of the pathways to overcome stalled replication, in which specific polymerases (TLS polymerase) perform bypass synthesis across DNA damage. This article gives a brief overview of plant TLS polymerases. In Arabisopsis, DNA polymerase (Pol) ζ, η, κ, θ, λ and Reversionless1 (Rev1) are shown to be involved in the TLS. For example, AtPolη bypasses UV-induced cyclobutane pyrimidine dimers in vitro. Disruption of AtPolζ or AtPolη increases root stem cell death after UV-irradiation. These results suggest that AtPolζ and ATPolη bypass UV-induced damage, prevent replication arrest, and allow damaged cells to survive and grow. In general, TLS polymerases have low fidelity and often induce mutations. Accordingly, disruption of AtPolζ or AtRev1 reduces somatic mutation frequency, whereas disruption of AtPolη elevates it, suggesting that plants have both mutagenic and less mutagenic TLS activities. The stalled replication fork can be resolved by a strand switch pathway involving a DNA helicase Rad5. Disruption of both AtPolζ and AtRAD5a shows synergistic or additive effects in the sensitivity to DNA-damaging agents. Moreover, AtPolζ- or AtRev1-disruption elevates homologous recombination frequencies in somatic tissues. These results suggest that the Rad5-dependent pathway and TLS are parallel. Plants grown in the presence of heat shock protein 90 (HSP90)-inhibitor showed lower mutation frequencies, suggesting that HSP90 regulates mutagenic TLS in plants. Hypersensitivities of TLS-deficient plants to γ-ray and/or crosslink damage suggest that plant TLS polymerases have multiple roles, as reported in other organisms.